Effectiveness of school-based mental health programs on mental health among adolescents - Fariba Shahraki-Sanavi; Alireza Ansari-Moghaddam; Mahdi Mohammadi; Nour-Mohammad Bakhshani; Hamid Salehiniya (Wolters Kluwer Medknow Publications, 2020)
AIM: This study aimed to investigate the effect of school-based interventions on mental health among adolescents in the southeast of Iran. METHODS: This interventional quasi-experimental study included a total of 420 adolescent girls studying 10th grade in the public schools of Zahedan, Iran. Data were collected using general health questionnaire-28 questionnaire. After pretest, multidimensional interventions (individual education, group education, individual consultations, modern education, and parents' educational packages) were given to the intervention group from October 2015 to June 2016. After a 3-month interval, the posttest was conducted in October 2016. Data were analyzed by covariance analysis. RESULTS: There was a significant statistical difference between the changes in the mental health scores after the intervention among the two study groups (P < 0.05). Furthermore, after the intervention, moderate-to-severe mental health problems decreased considerably among the students in the intervention group compared to controls. The greatest impact was on individual psychological counseling. CONCLUSIONS: The results of the study showed that by applying group training and individual counseling in the schools improves mental health. Therefore, identifying student problems and parent-teacher cooperation as well as consulting with specialist counselors can be effective in providing practical and effective solutions in this regard. Therefore, findings suggest that prioritizing mental health and taking action on the field are of utmost importance.